Kekuatan Mengikat Perjanjian Clickwrap dan Browsewrap dalam Perspektif Hukum Perjanjian di Indonesia - Titik Sri Hayati; Miftakhul Huda (Jurnal Hukum Lex Generalis, 2025)
The development of information technology has influenced contract law, particularly in electronic transactions such as clickwrap and browsewrap agreements. This study examines the binding force of both agreement types from the perspective of Indonesian contract law and core legal principles such as freedom of contract and good faith. Using a normative juridical method and both statutory and conceptual approaches, the study analyzes relevant legislation and finds that clickwrap agreements are more binding due to explicit consent, while browsewrap agreements are often disputed due to the lack of clear user assent. For validity, general contract requirements and information transparency must be fulfilled. This research recommends updating electronic contract regulations and strengthening the principle of informed consent in digital transactions to ensure legal certainty.